Alpha-synuclein spreading in Parkinson’s disease - Recasens, Ariadna; Dehay, Benjamin (Frontiers in Neuroanatomy, 2014)
Formation and accumulation of misfolded protein aggregates are a central hallmark of several neurodegenerative diseases. In Parkinson’s disease (PD), the aggregation-prone protein alpha-synuclein (α-syn) is the culprit. In the past few years, another piece of the puzzle has been added with data suggesting that α-syn may self-propagate, thereby contributing to the progression and extension of PD. Of particular importance, it was the seminal observation of Lewy bodies (LB), a histopathological signature of PD, in grafted fetal dopaminergic neurons in the striatum of PD patients. Consequently, these findings were a conceptual breakthrough, generating the “host to graft transmission” hypothesis, also called the “prion-like hypothesis.” Several in vitro and in vivo studies suggest that α-syn can undergo a toxic templated conformational change, spread from cell to cell and from region to region, and initiate the formation of “LB–like aggregates,” contributing to the PD pathogenesis. Here, we will review and discuss the current knowledge for such a putative mechanism on the prion-like nature of α-syn, and discuss about the proper use of the term prion-like.